The Effect of Perceived Service Quality, Perceived Value, Destination Image, Attitude to Visiting Behavior, Tourist Satisfaction on Tourist Loyalty - Muhammad Reza Islamy; Juliani D. Trisnawati; Siti Rahayu (Journal of Entrepreneurship and Business, 2022)
This study aims to determine the effect of perceived service quality, perceived value, destination image, attitude to visiting behavior, tourist satisfaction on tourist loyalty of Teluk Hijau beach in Banyuwangi, East Java tourists. Teluk Hijau beach is one of the tourist attractions in Banyuwangi, which is known as a hidden paradise. It has a green bay with a unique form of white sand that can spoil the tourists’ eyes and has more tourists than other beaches in Banyuwangi. This research is based on causal research, which was tested empirically using questionnaire data from 150 respondents. The research analysis used Structural Equation Modeling (SEM) with SPSS 18 and AMOS 22 software. The results show that perceived service quality and perceived value have a significant effect on destination image, and destination image, attitude to visiting behavior, and tourist satisfaction have a significant effect on tourist loyalty.